Garlic Capital of the World : Gilroy, Garlic, and the Making of a Festive Foodscape - Adema, Pauline (Book collections on Project MUSE., 2009)
According to Pauline Adema, you smell Gilroy, California, before you see it. In Garlic Capital of the World, the folklorist and culinary anthropologist examines the role of food and festivals in creating a place brand or marketable identity. The author scrutinizes how Gilroy, California, successfully transformed a negative association with the pungent bulb into a highly successful tourism and marketing campaign. This book explores how local initiatives led to an iconization of the humble product in Gilroy. The city, a well-established agricultural center and bedroom community south of San Fra.